2019
DOI: 10.1029/2018ja026115
|View full text |Cite
|
Sign up to set email alerts
|

The Intense Substorm Incidence in Response to Interplanetary Shock Impacts and Influence on Energetic Electron Fluxes at Geosynchronous Orbit

Abstract: The interaction between interplanetary (IP) shocks and the Earth's magnetosphere would generate/excite various types of geomagnetic phenomena. In order to analyze what kind of IP shock is more likely to trigger intense substorms (SME/AE > 1,000 nT) and how the energetic electrons response to intense substorms at geosynchronous orbit, we perform a systematic survey of 246 IP shock events using SuperMag and LANL observations between 2001 and 2013. The statistical analysis shows that intense substorms (SME > 1,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Liu and Zong (2015) emphasized the critical role of the radial gradient of phase space density (PSD) in the change of electron fluxes by the compressional effect of IP shock. Ma, Zong, and Liu (2019) found softer energy distributions of electrons during intense substorms driven by IP shocks.…”
Section: Introductionmentioning
confidence: 99%
“…Liu and Zong (2015) emphasized the critical role of the radial gradient of phase space density (PSD) in the change of electron fluxes by the compressional effect of IP shock. Ma, Zong, and Liu (2019) found softer energy distributions of electrons during intense substorms driven by IP shocks.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al. (2019) further found that during intense substorms triggered by IP shocks, the electron spectrum index in geosynchronous orbits became significantly larger.…”
Section: Introductionmentioning
confidence: 96%
“…Yue et al (2017) noted that after the shock impingement, chorus waves intensified in the postmidnight to the prenoon sector, while the plasmaspheric hiss decreased on the dayside and intensified during night (however, see the contrary findings in Tsurutani et al 2019 andMa et al 2022). Ma et al (2019) found that for shock-triggered substorms with SME > 1000 nT (including both traditional substorms and supersubstorms), E < 200 keV electron fluxes increased significantly. At the same time, >200 keV electron fluxes decreased.…”
Section: Introductionmentioning
confidence: 98%
“…It is well recognized that local midnight-sector substorms (Akasofu 1964) are often triggered by interplanetary shock impingements onto the magnetosphere (Heppner 1955;Schieldge & Siscoe 1970;Kawasaki et al 1971;Burch 1972;Kokubun et al 1977;Akasofu & Chao 1980;Chua et al 2001;Boudouridis et al 2003;Tsurutani & Zhou 2003;Liou et al 2004;Yue et al 2010Yue et al , 2011Yue et al , 2016Ma et al 2019;Oliveira et al 2021;Zong et al 2021). , using Polar UV data (Torr et al 1995), have shown that midnight-sector substorm onsets started within ∼2 minutes of the shock compression of the magnetosphere, and that the energy for shock-induced substorms could be provided by precursor interplanetary magnetic field (IMF) southward (B s ) components up to ∼1.5 hr prior to the shock arrival.…”
Section: Introductionmentioning
confidence: 99%